2019
DOI: 10.1177/1758573219864101
|View full text |Cite
|
Sign up to set email alerts
|

Partial articular supraspinatus tendon avulsion: Should we repair? A systematic review of the evidence

Abstract: Introduction Partial articular sided rotator cuff tears are described as being a common cause of shoulder pain and to have a significant impact of patient quality of life. The natural history of partial articular supraspinatus tendon avulsion lesions is not clearly defined and there is limited evidence to determine optimal management. Aims To perform a systematic review of the literature regarding the evidence for partial articular supraspinatus tendon avulsion repair and to determine whether there is any diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…A recent systematic review showed that no evidence exists to determine which tears are stable and which may progress in the partial articular side rotator cuff tears. 41 However, both-sided partial tears should be differently approached, and transtendon suture bridge repair showed favorable outcomes at the midterm follow-up in our study. 41 The strength of our study is that arthroscopy confirmed the presence of both-sided PTRCT among the symptomatic PTRCT, and the integrity of the rotator cuff at a mean of 11 months postoperatively was assessed on MRI scans according to the Sugaya classification, which can be used to objectively grade the repair status.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A recent systematic review showed that no evidence exists to determine which tears are stable and which may progress in the partial articular side rotator cuff tears. 41 However, both-sided partial tears should be differently approached, and transtendon suture bridge repair showed favorable outcomes at the midterm follow-up in our study. 41 The strength of our study is that arthroscopy confirmed the presence of both-sided PTRCT among the symptomatic PTRCT, and the integrity of the rotator cuff at a mean of 11 months postoperatively was assessed on MRI scans according to the Sugaya classification, which can be used to objectively grade the repair status.…”
Section: Discussionmentioning
confidence: 52%
“…41 However, both-sided partial tears should be differently approached, and transtendon suture bridge repair showed favorable outcomes at the midterm follow-up in our study. 41 The strength of our study is that arthroscopy confirmed the presence of both-sided PTRCT among the symptomatic PTRCT, and the integrity of the rotator cuff at a mean of 11 months postoperatively was assessed on MRI scans according to the Sugaya classification, which can be used to objectively grade the repair status. In a study of 249 cadavers, 13% had partial-thickness tears, in which 18% were bursal, 27% were articular, and 55% were intratendinous partial tears.…”
Section: Discussionmentioning
confidence: 52%
“…Several systematic reviews have shown that both techniques can improve shoulder function in the same way. 13 , 14 , 15 The advantages of trans-tendon repair are the preservation of the intact tendon and superior biomechanical strength. 10 , 11 However, there is a risk that the tendon will become overtensioned and that the technique will create tendon bunching on the bursal side, resulting in imbalanced tendon tension.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Nevertheless, systematic reviews have shown that both techniques can improve shoulder function in the same way. 13 , 14 , 15 We propose an all-inside arthroscopic trans-tendon repair technique of PASTA lesion without bunching of the bursal side of the tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Partial-thickness rotator cuff tears (PTRCTs) are common injuries that may cause pain through normal range of motion and shoulder dysfunction in affected patients. 24,36 Over 70% of patients undergoing surgical treament for rotator cuff tears were diagnosed with PTRCTs through arthroscopy, and the overall prevalence rate of PTRCTs in the population was 13% to 40% 24,28,33,40 ; however, the ideal repair techniques for bursal-sided PTRCTs remain controversial. 35,36 Two main techniques have been reported: conversion to a full-thickness tear followed by repair (tear completion repair [TCR]) and in situ repair (ISR) with preservation of the remaining articular-sided tendon.…”
mentioning
confidence: 99%